Search for neutral hydrogen with high negative velocities ejected from the galactic center - Mirabel Miquele, Igor Félix (1976)
A search for neutral hydrogen in the velocity range −300>V>−1000 km s−1 has been made in the zone around the galactic nucleus. Observations of 100 points reveal no neutral hydrogen at such high velocities, with brightness temperatures exceeding 0.25 K in the latitude range |b|<1°, and 0.20 K for |b|≥1°.